Effects of methyl cellulose‐based coating on physiochemical properties and chemical hazards of Chinese fried dough cake during storage. (22nd June 2021) - Han, Lipeng; He, Ye; Wang, Shujie; Cheng, Weiwei; Ma, Lukai; Liu, Guoqin; Han, Dongxue; Niu, Li
Abstract: Coating has been used as a practical method to ensure the physiochemical properties and reduce the chemical hazard of fried foods. Methyl cellulose (MC) was used as a coating material to pretreat Chinese fried dough cake (CFDC) before frying. The results showed that the water content, hardness and L* value of the 1% MC coated sample were 31.67%, 848.54 g and 51.62, respectively, at the seventh day at 25 °C. Coating contents 1% MC could reduce the oil content, hardness, and extent of browning and improve the physiochemical properties of CFDC on 7 days of storage. Coating contents 1% MC also reduced the acid value, peroxide value, p‐anisidine value, malondialdehyde content, 4‐hydroxy‐2‐(E)‐hexenal content, 4‐hydroxy‐2‐(E)‐nonenal content, acrylamide content and glycidyl ester content in CFDC on 7 days of storage. Our work contributes to the control of the oil content and chemical hazards for fried food during storage by applying an edible coating. Abstract : Methyl cellulose‐based coating can reduce the chemical hazard of Chinese fried dough cake.